Memahami Teori Inteligensi Ganda Howard Gardner Dan Aplikasinya Dalam Proses Pembelajaran Di Sekolah Dewasa Ini - Emanuel Haru (STIPAS St. Sirilus Ruteng, 2017)
Howard Gardner is well-known because of his multiple intelligences theory. According to him, there are many kinds of intelligences. At least, there are nine kinds of intelligences. And all these intelligences owned by everyone with different grade/ quality. Commonly, people proud when his/ her intelligence quotient (IQ) is high. And people think that the high intelligence quotient (IQ) is the main guarantee to reach the successful. Actually, one’s successful not only determined by intelligence quotient (IQ), but by all these intelligences. In this case, we must know what benefit of knowing the various intelligences in ourselves. Especially, it is important for a teacher to know all kinds of intelligences in his/ her students. Thus, in learning process, a teacher not only pay attention to a certain intelligence (such as intelligence quotient), but he/ she also has to pay attention to many kinds of intelligences. By this way, a teacher accomodate all students in exploring their capabilities.